2013
DOI: 10.2355/isijinternational.53.375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Fatigue Strength of Intercritically Austenitized and Austempered Ductile Irons with Dual Matrix Structures

Abstract: In the present study the fatigue strength of austempered ductile irons with dual matrix structures (ADI with DMS) has been studied for an unalloyed ductile cast iron. For this purpose, specimens were intercritically austenitized (partially austenitized) in two phase region (α + γ ) at various temperatures (810°C, 820°C and 830°C) for 20 minutes and then quenched into salt bath held at austempering temperature of 315°C and 375°C for 120 minutes and then air cooled to room temperature to obtain various ausferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
6
0
4
Order By: Relevance
“…Thus, a combination of high strength and high ductility is not possible to produce in conventionally processed ADI. Therefore, in recent years many researchers [11][12][13][14][15][16][17][18] have used an intercritical austempering process to improve the ductility of ADI.…”
Section: Hcmentioning
confidence: 99%
“…Thus, a combination of high strength and high ductility is not possible to produce in conventionally processed ADI. Therefore, in recent years many researchers [11][12][13][14][15][16][17][18] have used an intercritical austempering process to improve the ductility of ADI.…”
Section: Hcmentioning
confidence: 99%
“…Bu sonuç literatürle paralellik göstermektedir [2, 10,[27][28][29][30][31][32][33][34]. Östemperleme ile yorulma sınırındaki bu artış, ince ösferritik yapının perlitik yapıya göre yorulma çatlaklarının ilerlemesine karşı direncini artırdığına dayandırılmaktadır [10,[27][28][29][30][31][32][33][34][35][36].…”
Section: Yorulma öZellikleri (Fatigue Properties)unclassified
“…Ductile cast iron (DCI) 1,2) has attracted attention as a material that can replace welded joints. 3) In our previous experimental study, the authors revealed that the fatigue strength of DCI joints is about 2 times or more larger than that of non-load-carrying cruciform welded joints.…”
Section: Introductionmentioning
confidence: 99%